2015
DOI: 10.1101/030536
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The zebrafishgoosepimples/myosin Vbmutant exhibits cellular attributes of human microvillus inclusion disease

Abstract: Bullet points (Key findings):• myosin Vb is expressed in the zebrafish intestine.• goosepimples/myosin Vb function is essential for the morphogenesis, cell shape modulation, secretion of glycoproteins and prevention of the formation of microvillus inclusions in the zebrafish intestine.• The function of myosin Vb in the intestine is conserved between fish and humans.• The goosepimples mutant is a good animal model for microvillus inclusion disease in humans. Grant Sponsor: Wellcome Trust-DBT India alliance (MS;… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This age also corresponds to the period when higher mortality was observed in Dr-VSP -/larvae (Figure 5A). We measured key parameters that represent cell morphology: central height, apical width, basal width, and microvillus length (Sidhaye et al, 2016). The measurement revealed that Dr-VSP -/-LREs were significantly shorter in all other parameters except for the microvillus length (Figure 7B).…”
Section: Dr-vsp Maintains Intact Lre Morphologymentioning
confidence: 98%
See 1 more Smart Citation
“…This age also corresponds to the period when higher mortality was observed in Dr-VSP -/larvae (Figure 5A). We measured key parameters that represent cell morphology: central height, apical width, basal width, and microvillus length (Sidhaye et al, 2016). The measurement revealed that Dr-VSP -/-LREs were significantly shorter in all other parameters except for the microvillus length (Figure 7B).…”
Section: Dr-vsp Maintains Intact Lre Morphologymentioning
confidence: 98%
“…Quantification of cellular dimensions of LREs was done based on the previous procedure (Sidhaye et al, 2016). We performed immunostaining with Acti-stain TM 488 Phalloidin (Cytoskeleton, USA) and anti-Na + -K + ATPase Antibody (Ab76020; Abcam, USA) to outline individual cell (Figure 7A).…”
Section: Parameter Analysis Of Larval Enterocytesmentioning
confidence: 99%